A study of the characteristics of thunderstorm - Dayangku Siti Nur Baizura, Awangku Matali (2013)
In the period of 2010-2012, there are several cases reported where thunderstorms that occurred in the North of Peninsular Malaysia causes damage to the structure of the building, especially the roof and other structural parts of the building. There are several factors, which contribute to the thunderstorm occurrences such as the location and topography area. In Malaysia, there are two types of monsoon, which are Northeast Monsoon and Southwest Monsoon. Southwest monsoon blows from April-September and the Northeast monsoon occurs from November-March while April and October are the inter-monsoon. By using GIS technique, thunderstorm events that reported are collected as a data to establish a database by creating a database of locations of thunderstorms in the Northern region of Peninsular Malaysia and the related casualties or damages caused by thunderstorm. The results shows that the higher rainfall intensity, the larger radial thunderstorm covered at specific location. The correlation of these two variables shows the positive correlation. Therefore, this technique can be used to estimate thunderstorm radial based on rainfall intensity.